2018
DOI: 10.1002/osp4.280
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and weight misperception among adults in the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study

Abstract: SummaryObjectivePrior studies have suggested that weight misperception – underestimating one's actual weight – may be associated with reduced engagement in weight loss programmes, decreasing the success of initiatives to address obesity and obesity‐related diseases. The purpose of this study was to examine the factors associated with weight misperception among Eastern Caribbean adults and its influence on engagement in weight control behaviour.MethodsData from the Eastern Caribbean Health Outcomes Research Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
(63 reference statements)
5
20
0
Order By: Relevance
“…Some demographic factors seem to influence weight underestimation. In our study, underestimation increased slightly by age, and this is also observed in several other studies 4 38 39. Higher education, which is often considered a proxy for higher socioeconomic status, was protective of underestimation in the non-Sami with overweight/obesity, and this is in accordance with findings of previous studies 4 31 38 39.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some demographic factors seem to influence weight underestimation. In our study, underestimation increased slightly by age, and this is also observed in several other studies 4 38 39. Higher education, which is often considered a proxy for higher socioeconomic status, was protective of underestimation in the non-Sami with overweight/obesity, and this is in accordance with findings of previous studies 4 31 38 39.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy between women and men highly agrees with most studies published, and many of these are based on different ethnic populations 4 31 35–37. A study of Caribbean adults aged >40 years, however, showed equal sex distribution 38. The authors of the latter study argue that part of the explanation for the observed equal distribution between men and women may be that the general view within this community is that overweight is actually desirable.…”
Section: Discussionsupporting
confidence: 83%
“…This unique partnership created the ECHORN Cohort Study (ECS), the first regional cohort study. 18,19 The ECS is an ongoing prospective cohort study that seeks to improve our understanding of early predictors and risk factors for NCDs in Caribbean and Caribbean-descent populations. With 3,000 cohort participants, the ECS collects data using survey tools, clinical assessment, and blood testing.…”
Section: Methodsmentioning
confidence: 99%
“…Collected data include a wide range of participant and household characteristics, past medical diagnoses, health biomarkers and health outcomes, and health care utilization. 18,19 One of the main aims of the Yale-TCC is to create a mechanism to share de-identified and aggregated population-level data from the ECS with community stakeholders and ECS participants. Aligned with a precision medicine approach, the Yale-TCC seeks also to merge publicly available population-level, health-related contextual data (such as social determinants of health, environmental data, or others) with biological, clinical and health-related data from the ECS participants.…”
Section: Methodsmentioning
confidence: 99%
“…There are fewer studies of weight perception conducted on adults. A simple Google Scholar search of titles for "weight perception" or "weight misperception" in adults, since 2015, yielded just eight relevant articles [15,[21][22][23][24][25][26][27]. There are no studies extant on BMI perception.…”
Section: Introductionmentioning
confidence: 99%